The Rally-Intensive Campaign: A Distinct Form of Electioneering in Sub-Saharan Africa and Beyond. (October 2019) - Paget, Dan
I consider how to characterize and classify election campaigns in sub-Saharan Africa. I revisit the typology proposed by Pippa Norris, which distinguishes between premodern, modern, and postmodern campaigns. This typology, and others like it, homogenizes ground campaigns. Ground campaigns only feature by virtue of their centrality in premodern campaigns and their peripherality in modern and postmodern campaigns. I argue that the prominence of the rally varies across ground campaigns. By trivializing rallies, current typologies obscure this variation between African campaigns and between campaigns in sub-Saharan Africa and the rest of the world. To accommodate these differences, I propose a schema of campaign ecologies, adapted from Norris' own, which incorporates a distinct ideal-type: the rally-intensive campaign. This revision internationalizes this hitherto Western-bound typology and may illuminate the features of campaigns in other middle- and low-income countries too. Equally, it throws into relief differences between historic premodern campaigns in Western countries. I contend that rally-intensiveness is a definitive feature of election campaigns from which other features stem. To illuminate such typical features, I study Tanzania, which has the most rally-intensive campaigns in Africa. I draw on ethnographic research and original survey data to identify the four following typical features of the rally-intensive campaign. Local as well as national leaders hold rallies frequently. Local rallies are better attended in aggregate than national ones, and accordingly, campaign contact is direct. Mass meetings dwarf the canvass as a means of campaign contact, and local party networks concentrate their efforts on "producing" rallies.